Subcomponent Modal Tests In The H135-Production Line To Further Improve Finite-Element Model Updating Background, Experimental Setup And Results Of Extensive Vibration Tests - Knebusch, J.; Soal, K.; Meier, D.; Meier, T.; Altug, M.N.; Dieterich, O.; Böswald, M. (My University, 2024)
Helicopters are designed to be as light as possible, in order to increase flight performance, to decrease the environmental footprint and to minimize operating costs. However, lightweight structures are generally susceptible to vibrations. As a byproduct of the lift and thrust created by the main rotor, oscillatory loads are inevitably introduced into the airframe via the main rotor hub and the main gear box. This combination of lightweight design and dynamic loads makes structural dynamics of the airframe a relevant topic in helicopter design. In recent years, the simulation techniques to calculate the aeromechanic forces of the rotors system have become reasonably accurate. In spite of these advances, simulation models of helicopter airframes are not yet fully capable to predict the propagation of vibrations due to the introduced forces. The finite element (FE) models used for these simulations are created during the design phase and continuously adapted during design iterations. At the end of the design phase, a prototype of the optimized design is built. Its structural dynamic characteristics are determined in a so-called shake test. The result of the shake test are experimentally determined modal parameters like eigenfrequencies, damping ratios and mode shapes which can be compared with simulation results obtained from the FE models. If the deviations between test and simulation are too large, the FE models must be adapted to reality. However, a complete helicopter is an intricate system and the possible sources of modelling errors in the FE models can be numerous. Therefore, this goal is difficult to achieve. Due to this known limitation, Airbus Helicopters and DLR jointly developed a new approach for the improvement of dynamic models of helicopter fuselage. The key idea is to perform subcomponent modal tests on a successively built serial production helicopter in the assembly line. These tests took place during normal manufacturing operations in the production line and are used to validate the respective subcomponents in the FE model. As an outcome of this validation process, poor modeling assumptions can be identified and an accurate simulation model of the entire helicopter can be synthesized. In order to proof the feasibility of this approach, an extensive measurement campaign was conducted on an H135 in the assembly line at Airbus Helicopters Germany in 2022. In the process, modal tests were performed on the successively assembled helicopter at 10 production stations. This publication is intended to show the experimental setup, as well as results of this extensive modal test campaign. Even though the approach was demonstrated to be feasible and effective on a well-established helicopter model (i.e. H135), it was developed for application on future helicopter developments.